3D Subsurface Modeling of Multi-Scenario Rock Property and AVO Feasibility Cubes—An Integrated Workflow - Avseth, Per; Lehocki, Ivan (Frontiers in Earth Science, 2021)
A novel inter-disciplinary methodology for generation of rock property and AVO feasibility maps or cubes to be used in subsurface characterization and prospect de-risking is presented. We demonstrate the workflow for 1D, 2D and 3D cases on data from the Barents Sea, offshore Norway. The methodology enables rapid extrapolation of expected rock physics properties away from well control, along selected horizon, constrained by seismic velocity information, geological inputs (basin modelling, seismic stratigraphy and facies maps) and rock physics depth trend analysis. The workflow should allow for more rapid, seamless and geologically consistent subsurface mapping and de-risking of prospects in areas with complex geology and tectonic influence. The AVO feasibility results can furthermore be utilized to generate non-stationary training data for AVO classification.